PEMBELAJARAN PANCASILA DAN KEWARGANEGARAAN MENJADI PENYARING PENGARUH GLOBALISASI MAHASISWA - Kirani Sisca Damayanti; Adela Herlina Grace Nasution; Bhisma Oktafian Ilhamsyah; Ridho Achsyani; Nurlintang Anugerah Gustianti; Tranggono Tranggono (Gapenas Publisher, 2023)
Provides an overview of the relationship between Pancasila Education, citizenship, using the views and spirit of nationalism as a means of filtering globalization which diminishes the spirit of nationalism of the nation's generation, which is the goal of the researchers. Using quantitative methods with correlation techniques in this study. The researchers obtained the data through questionnaires and student sample tests. The researcher suggests: 1. The implementation of Pancasila which is studied in the education community as the main general subject of character education has actually been carried out well and in line with national policy objectives. 2. Students must have a good understanding of love for the motherland and love for the motherland. 3. The application of Pancasila studies in the country as a general core study is very closely related to the understanding and promotion of student patriotism which is currently facing the onslaught of globalization